2010
DOI: 10.3138/cjccj.52.5.545
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Analysis of How Canadian Police Officers Administer the Right-to-Silence and Right-to-Legal-Counsel Cautions

Abstract: À l'aide d'un guide de codage contenant 78 éléments, on a évalué comment ont été émis les avertissements concernant le droit au silence et le droit à un conseiller juridique dans le cadre de 126 entrevues d'enquête (37 vidéos et 89 transcriptions). On a noté ces avertissements dans 87 % des vidéos et 83 % des transcriptions. Selon une analyse du débit de la parole, la vitesse de parole dépassait les taux acceptables permettant d'assurer une bonne compréhension orale de ces deux avertissements. Même si les aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 15 publications
1
24
0
2
Order By: Relevance
“…The findings reported here suggest that a similar problem exists with Canadian offenders and that they likely remain unprotected during interrogations (assuming the rights are merely recited off a police caution card like they were in this study; see Snook et al 2010). In addition, it is likely that many of the instances where rights were waived were invalid because the person waiving the rights simply did not understand what those rights were, and according to case law, the resulting statements could be ruled inadmissible in court (Marin 2004).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The findings reported here suggest that a similar problem exists with Canadian offenders and that they likely remain unprotected during interrogations (assuming the rights are merely recited off a police caution card like they were in this study; see Snook et al 2010). In addition, it is likely that many of the instances where rights were waived were invalid because the person waiving the rights simply did not understand what those rights were, and according to case law, the resulting statements could be ruled inadmissible in court (Marin 2004).…”
Section: Discussionmentioning
confidence: 66%
“…However, the results of the current study, in line with those from previous research (Fenner et al 2002;Grisso 1981), suggest that such an assumption is unwarranted. Along with the complexity of the cautions themselves mentioned earlier, one likely explanation for experience not leading to increased comprehension comes from some research suggesting that police interviewers rarely verify understanding when delivering the cautions and tend to recite the rights verbatim (see Snook et al 2010). The lack of feedback provided to suspects and accused persons about the comprehension of the rights means that possible misunderstandings or misconceptions are not identified and dealt with and that offenders, therefore, do not fully understand their rights despite past experience with police cautions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Snook et al (2010) found that police investigators often read the right to silence at a rate so fast as to preclude comprehension, and that they rarely attempt to verify that suspects understand their rights. This may reflect an inherent dilemma for police when warning suspects of their legal rights.…”
Section: Discussionmentioning
confidence: 98%
“…Notes 1 Une étude a démontré que les policiers communiquent toujours des mises en garde oralement lorsqu'ils font affaire avec des adultes (Snook, Eastwood et MacDonald 2010), ce qui indique que les formulaires de déclaration et de renonciation aux droits pour adolescents pourraient également être présentés oralement. De plus, les conversations informelles avec des policiers révèlent qu'ils lisent presque toujours à haute voix les formulaires de déclaration et de renonciation aux droits pour adolescents et leur demandent rarement de les lire.…”
Section: Résultatsunclassified